(untitled) (Jurnal Proaksi, 2023)
Abstract The level of effectiveness of tax payments in Indonesia is currently still not optimal. One of the reasons is that there is still tax aggressiveness in technology companies.This study aims to examine the effect of related transactions consisting of sales, purchases, and loan transactions on tax aggressiveness. Tax aggressiveness is measured using the Effective Tax Rate (ETR). The data used in this study is secondary data from the financial reports of technology sector companies listed on the IDX for 2020-2021. The research sample was taken using purposive samplings to obtain much as 39 data from 70 companies selected as samples. The results of this study indicate that related sales transactions and related purchase transactions do not have a significant effect on tax aggressiveness, while the results of related loan transactions have a significant effect on tax aggressiveness. Keywords: Transfer Pricing, Tax Aggressiveness